The Impact of Social Media on Political Awareness in Libya: A Field Study of Libyan Society (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the impact of social media use on the level of political awareness among Libyan citizens in light of the political and social transformations the country has witnessed since 2011. The study adopted a descriptive-analytical approach and used an electronic questionnaire consisting of 50 items distributed across six main axes, according to a five-point Likert scale. The sample included 350 participants selected using stratified random sampling from various Libyan cities. The results of the statistical analysis using SPSS (version 28) showed a statistically significant positive correlation between the intensity of social media platform use and the level of political awareness (r = 0.67, d < 0.01). Furthermore, the results of multiple regression revealed that the variable "exposure to diverse political content" was the most influential in explaining the variance in political awareness (β = 0.42, d < 0.001). The study recommended integrating digital media literacy into Libyan educational curricula and strengthening fact-checking mechanisms to enable citizens to critically engage with online political content.
Keywords: social media, political awareness, Libya, statistical analysis, Likert scale, civic participation.